2015
DOI: 10.1136/bmjopen-2015-008964
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood walkability, daily steps and utilitarian walking in Canadian adults

Abstract: ObjectivesTo estimate the associations of neighbourhood walkability (based on Geographic Information System (GIS)-derived measures of street connectivity, land use mix, and population density and the Walk Score) with self-reported utilitarian walking and accelerometer-assessed daily steps in Canadian adults.DesignA cross-sectional analysis of data collected as part of the Canadian Health Measures Survey (2007–2009).SettingHome neighbourhoods (500 m polygonal street network buffers around the centroid of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 63 publications
3
42
3
3
Order By: Relevance
“…31 Hajna and colleagues examined adult respondents to the Canadian Health Measures Survey cycle 1, a subset of our study population, but they did not find significant associations between walkability and objectively measured step counts. 49 Our positive results differ from these null findings, possibly because of the following: the majority of daily physical activity is light physical activity; therefore, studies that assessed "total physical activity" or "step counts" captured mostly light physical activity. 4,5 Common light physical activities include light household cleaning and walking around workplaces, 16 which are not expected to be associated with neighbourhood walkability.…”
contrasting
confidence: 87%
See 1 more Smart Citation
“…31 Hajna and colleagues examined adult respondents to the Canadian Health Measures Survey cycle 1, a subset of our study population, but they did not find significant associations between walkability and objectively measured step counts. 49 Our positive results differ from these null findings, possibly because of the following: the majority of daily physical activity is light physical activity; therefore, studies that assessed "total physical activity" or "step counts" captured mostly light physical activity. 4,5 Common light physical activities include light household cleaning and walking around workplaces, 16 which are not expected to be associated with neighbourhood walkability.…”
contrasting
confidence: 87%
“…Two recent studies in Canada analyzed national-level populations using the Walk Score metric to assess walkability. 31, 49 Thielman and colleagues found positive associations between walkability and self-reported total physical activity among people aged 30-64 years, but they did not find associations among those aged 12-17, 18-29 or 65 years and older. 31 Hajna and colleagues examined adult respondents to the Canadian Health Measures Survey cycle 1, a subset of our study population, but they did not find significant associations between walkability and objectively measured step counts.…”
Section: Cmaj Open Cmaj Open 4(4) E725mentioning
confidence: 98%
“…No studies were specifically undertaken in the three territories (Nunavut, Northwest Territories or Yukon), though data from the territories were included in two stud ies that used national data. 43,44 Among studies that reported mean age (n = 11), the lowest mean age was 33.6 years 46 and the highest mean age was 75 years. 47 Six study samples involved only older adults (≥50 years).…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…trips by foot) reported in travel dia ries. 40,46,48,49,58,59 Three studies measured walking using selfreports and accelerom eters; 40,43,49 one study captured steps/day using pedometers; 60 and two studies audited pedestrian activity using auto mated counters. 51,52 Walking undertaken in the past seven days was most often assessed (n = 16), although walking in the previous day (n = 3), previous 14 days (n = 1) and previous three months (n = 3) were also captured.…”
Section: Measurement Of Walkingmentioning
confidence: 99%
“…Yürüme yetişkinler arasında fiziksel aktivitenin en yaygın ve tercih edilen şeklidir (34). Yürüme aynı zamanda, tipik sedanter yaşlı yetişkinler arasında da nispeten yaygın olan bir fiziksel aktivitedir.…”
Section: Fiziksel Aktivite Ve Sağlıklı Yaşlanmaunclassified